COST PERFORMANCE ANALYSIS OF INTEGRATED LABORATORY BUILDING CONSTRUCTION BASED ON BUDGET VARIANCE ANALYSIS - Tahrir, Muhammad; Teguh Rizali Zahroni; Muh. Akshar; Risna Nona (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study examines the cost performance of the Integrated Laboratory Building construction project by comparing the 2023 and 2025 Cost Budget Plans (Rencana Anggaran Biaya/RAB). The objective is to identify cost variances in each major work category and evaluate the efficiency of budget utilization. A descriptive quantitative approach was employed using official RAB documents from both periods as the primary data source. Variance analysis was conducted by calculating absolute and percentage differences between the estimated and contract values. The results indicate that the total budget in 2025 decreased by IDR 1.35 billion (2.91%) compared with the 2023 estimate. Significant cost increases occurred in electrical panel works (430.3%) and plumbing systems (152.7%), while the greatest efficiencies were achieved in façade works (13.6%) and air-conditioning systems (13.8%). Overall, the 2025 contract value achieved an efficiency level of 97.09% relative to the estimated budget, indicating good and efficient cost performance in project implementation.